Differential effects of isoflurane on auditory and visually evoked potentials in the cat - Bao, Xiaohan; Barnes, Paisley; Lomber, Stephen G. (Frontiers in Systems Neuroscience, 2024)
Evoked potentials can be used as an intraoperative monitoring measure in neurological surgery. Auditory evoked potentials (AEPs), or specifically brainstem auditory evoked responses (BAERs), are known for being minimally affected by anesthetics, while visually evoked potentials (VEPs) are presumed to be unreliable and easily affected by anesthetics. While many anesthesia trials or intraoperative recordings have provided evidence in support of these hypotheses, the comparisons were always made between AEPs and VEPs recorded sequentially, rather than recorded at the same time. Although the logistics of improving data comparability of AEPs and VEPs may be a challenge in clinical settings, it is much more approachable in animal models to measure AEPs and VEPs as simultaneously as possible. Five cats under dexmedetomidine sedation received five, 10-min blocks of isoflurane with varying concentrations while click-evoked AEPs and flash-evoked VEPs were recorded from subdermal electrodes. We found that, in terms of their waveforms, (1) short-latency AEPs (BAERs) were the least affected while middle-latency AEPs were dramatically altered by isoflurane, and (2) short-latency VEPs was less persistent than that of short-latency AEPs, while both middle- and long-latency VEPs were largely suppressed by isoflurane and, in some cases, completely diminished. In addition, the signal strength in all but the middle-latency AEPs was significantly suppressed by isoflurane. We identified multiple AEP or VEP peak components demonstrating suppressed amplitudes and/or changed latencies by isoflurane. Overall, we confirmed that both cat AEPs and VEPs are affected during isoflurane anesthesia, as in humans.